2017
DOI: 10.1021/acs.orglett.7b02178
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic, Dioxirane-Mediated C–H Hydroxylation under Mild Conditions Using Oxone

Abstract: Dioxiranes are among the most selective and useful reagents for C(sp)-H hydroxylation, but the development of a general dioxirane-mediated catalytic method has been an elusive goal. A trifluoromethyl ketone catalyst in combination with Oxone is shown to enable the first dioxirane-mediated catalytic hydroxylations that approximate the reactivity and selectivity of isolated dioxiranes. The mild reaction conditions allow for selective 3° hydroxylation and 2° oxidation and are tolerant of acid-sensitive functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
0
32
0
1
Order By: Relevance
“…Furthermore, very recently,H ilinski and co-workers have employed trifluoromethyl ketones for the efficient CÀHa ctivation/hydroxylation of alkanes. [89] Havingi nm ind literaturek nowledge on perhydrates as oxidants, [54] Kokotos has identified as mall commerciallya vailable organic molecule that can provideasimilar activation mode. In their design, the key feature was thought to be activation of the carbonyl group of the ketone, and as an extension, simple hydration conditions would afford the hydrate of the ketone.…”
Section: 22-trifluoroacetophenone:a No Rganocatalyst For Alkene Oxmentioning
confidence: 99%
“…Furthermore, very recently,H ilinski and co-workers have employed trifluoromethyl ketones for the efficient CÀHa ctivation/hydroxylation of alkanes. [89] Havingi nm ind literaturek nowledge on perhydrates as oxidants, [54] Kokotos has identified as mall commerciallya vailable organic molecule that can provideasimilar activation mode. In their design, the key feature was thought to be activation of the carbonyl group of the ketone, and as an extension, simple hydration conditions would afford the hydrate of the ketone.…”
Section: 22-trifluoroacetophenone:a No Rganocatalyst For Alkene Oxmentioning
confidence: 99%
“…[78] In 2017, after extensive investigation, they reported a second-generation approachtoketone-catalyzed hydroxylation that addresses these limitations. [79] Indeed, the hydroxylation of the CÀHb ond wasa ccomplished by treatment with ac ommerciallya vailable alkyl trifluoromethyl ketone 48 combined with oxone as oxidant(Scheme20). [79] Addition of aw ater/hexafluoroisopropanol (HFIP) mixture as ac osolvent, according to Du Bois'sa pproach, [80] resultsi nd ecreasedr eaction times, expanded substrate scope, and enabled catalytic turnoveru nder conditions closer to the typical conditions for dioxirane-mediatedo xidations (e.g.,o xone/ NaHCO 3 ).…”
Section: Site-selective Càhbond Oxyfunctionalization In Total Synthesmentioning
confidence: 99%
“…[79] Indeed, the hydroxylation of the CÀHb ond wasa ccomplished by treatment with ac ommerciallya vailable alkyl trifluoromethyl ketone 48 combined with oxone as oxidant(Scheme20). [79] Addition of aw ater/hexafluoroisopropanol (HFIP) mixture as ac osolvent, according to Du Bois'sa pproach, [80] resultsi nd ecreasedr eaction times, expanded substrate scope, and enabled catalytic turnoveru nder conditions closer to the typical conditions for dioxirane-mediatedo xidations (e.g.,o xone/ NaHCO 3 ). Further,t hey also demonstrated that ah ighly valued characteristic of dioxirane reactivity is the full retentiono fs ite selectivity when used for the late-stage oxidation of highly complex, biologically relevant substrates.…”
Section: Site-selective Càhbond Oxyfunctionalization In Total Synthesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Ther eagents that are typically involved in these processes include heteroatomcentered radicals and radical ions,p hotoexcited species and photocatalysts (carbonyl compounds,polyoxometalates), biocatalysts (cytochrome P450 and oxygenases) and bioinspired catalysts,a swell as closed-shell species such as dioxiranes. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Ther eagents that are typically involved in these processes include heteroatomcentered radicals and radical ions,p hotoexcited species and photocatalysts (carbonyl compounds,polyoxometalates), biocatalysts (cytochrome P450 and oxygenases) and bioinspired catalysts,a swell as closed-shell species such as dioxiranes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available methods for the site-selective functionalization of aliphatic CÀHb onds,t hose based on hydrogen atom transfer (HAT) to radical or radical-like species play an important role. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Ther eagents that are typically involved in these processes include heteroatomcentered radicals and radical ions,p hotoexcited species and photocatalysts (carbonyl compounds,polyoxometalates), biocatalysts (cytochrome P450 and oxygenases) and bioinspired catalysts,a swell as closed-shell species such as dioxiranes.…”
Section: Introductionmentioning
confidence: 99%